Depletion imaging of Rydberg atoms in cold atomic gases - Ferreira-Cao, Miguel; Gavryusev, Vladislav; Franz, Titus; Ferracini Alves, Renato; Signoles, Adrien; Zürn, Gerhard; Weidemüller, Matthias (Journal of physics. B, Atomic, molecular and optical physics, 2020)
We present a depletion imaging technique to map out the spatial and temporal dependency of the density distribution of an ultracold gas of Rydberg atoms. Locally resolved absorption depletion, observed through differential ground state absorption imaging of a 87Rb cloud in presence and absence of pre-excited Rydberg atoms, reveals their projected two-dimensional distribution. By employing a closed two-level optical transition uncoupled from the Rydberg state, the highly excited atoms are preserved during imaging. We measure the excitation dynamics of the state of 87Rb, observing a saturation of the two-dimensional Rydberg density. Such outcome can be explained by the Rydberg blockade effect which prevents resonant excitation of close-by Rydberg atoms due to strong dipolar interactions. By combining the superatom description, where atoms within a blockade radius are represented as collective excitations, with a Monte Carlo sampling, we can quantitatively model the observed excitation dynamics and infer the full three-dimensional distribution of Rydberg atoms, that can serve as a starting point for quantum simulation of many-body dynamics involving Rydberg spin systems.
Gesehen am 21.04.2020